Development of Concealer X Packaging Using Kansei Engineering - Sari, Novi Purnama; Sinur, Valeri Vela; Suharto, Nurlita Pratiwi; Amri, Aulia (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2025)
Concealer x packaging still has shortcomings in its packaging from the applicator which makes it difficult to use, the packaging design is uncomfortable for consumers, and the visual design is less informative. This is a challenge in developing concealer x packaging by considering consumer preferences. The purpose of this study is to identify the concept and elements of packaging design according to consumer preferences. Kansei Engineering is one of the methods used to optimize the identification of consumer preferences. This method can capture consumer emotions in the form of Kansei words which are translated into concepts and elements of packaging design. Other supporting methods used are Principal Component Analysis (PCA) and Quantification Theory Type 1 (QTT1). The results obtained were 61 selected samples and 35 Kansei words. The samples and Kansei words were then evaluated by creating a semantic differential questionnaire for 30 respondents by purpose judgment sampling. The results of the concept obtained by the PCA method were 4 PCs with PC 2 selected as the practical standard because it had the highest R-square value of 0.911. The results of the packaging design elements obtained are X1.1 Strew X2.9 Concave X3.6 Jug X4.3 Half Tube X5.4 Heptagon X6.2 Brush and Sponge X7.5 Silicon X8.1 Fun X9.1 Small 1 - 5 gr X10.1 Under. The conclusion of the packaging design obtained has described practical packaging following the design concept and meets consumer preferences.